Acupuntura manual y variabilidad de la frecuencia cardíaca: efecto de la acupuntura en los puntos C7 y B6 - García García, José Luis (Universidad Autónoma Metropolitana, 2022)
Heart rate variability (HRV) is a physiological characteristic related to the influence of the autonomic nervous system (ANS) on heart rate, and is a valuable tool as a predictive and developmental factor for various disorders involving ANS disorders. Acupuncture is used as the sole treatment for various cardiovascular disorders. Points PC6 and to a lesser degree B6 are used in the treatment of various cardiovascular diseases as a sole or complementary measure. The aim of this research is to compare the effect of points C7 versus B6 on heart rate variability in healthy adults. Materials and methods An experimental, cross-sectional, comparative and open study was carried out. Twelve healthy volunteers were recruited and divided into two groups: the first to study the effect of C7 made up of 6 subjects (2/4 women / men) aged 26 ± 4.7 (mean ± SD); the second to study the effect of B6 made up of 6 subjects (5/1 women / men) aged 28 ± 6.5 (mean ± SD). The research protocol was approved by the Institution's Ethics Committee and adhered to the Declaration of Helsinki regarding biomedical research in humans. Each of the 12 participants was randomly assigned to one of the two experimental groups. Subjects remained at rest in supine position for a stabilization period of 5 min; then three 5-min recordings of the pre-acupuncture, transacupuncture, and post-acupuncture stages were made. To calculate the heart rate variability (HRV), an electrocardiographic record was made, which was amplified and digitized using the SphygmoCor equipment (AtCor Medical, Model EM3, Sydney, Australia) and stored in a computer. The frequency domain indices were low, high and the low / high ratio (LF, HF, LH / HF, respectively according to their acronym in English). Acupuncture needles (HBW Supply Inc., San Jacinto Hemet, CA, USA) with 0.30 x 40 mm in diameter and length, respectively, were used. The points were located in the traditional way and the needle was inserted perpendicular to the recommended depths; no additional stimulation was performed, and the needle remained inserted for 5 minutes. For the kinetic analysis of the changes in the heart rate produced by each of the five points, a continuous recording of the RR intervals was carried out during a period of 5 min using the Finometer instrument (Finapres Medical Systems, The Netherlands). Acupuncture was applied to each of the points studied during the 6-10 minute period of the recording. From the RR intervals, the heart rate was calculated; then the first derivative of the RR interval curve was obtained. Results The most notable results were as follows: acupuncture at C7 produced increases in the acupuncture and post-acupuncture periods. The use of the first derivative of the RR interval curve showed that the maximum speed of the increase of the RR intervals by the application of manual acupuncture at C7 occurred in the second 7.4. On the other hand, acupuncture in B6 did not cause significant changes in the HRV indices studied. Acupuncture in B6 produced a increase in the post-acupuncture period. The use of the first derivative of the RR interval curve showed that the maximum speed of the increase of the RR intervals by the application of manual acupuncture in B6 occurred in the second 46. The comparison of the effect of these points showed that C7 and B6 they initially caused an increase and a decrease in the duration of the RR intervals, respectively. The rapidity of the effect of C7 was greater than that of B6; while the magnitude of the effect of C7 was relatively greater than that of B6. Conclusions The application of acupuncture points C7 and B6 showed opposite effects on the duration of the RR intervals. Point C7 caused an increase in the duration of the RR intervals of faster appearance and greater relative intensity, with respect to the effect of decreasing the duration and relative intensity by acupuncture at point B6. Which is consistent with the clinical observations of a greater cardiovascular effect with the application of C7. None of the acupuncture treatments at C7 or BP6 caused significant changes in heart rate variability. Key words: heart rate variability, Heart 7, Spleen 6, acupuncture kinetics, RR intervals.; La variabilidad de la frecuencia cardíaca (VFC) es una característica fisiológica relacionada con la influencia del sistema nervioso autónomo (SNA) en la frecuencia cardíaca, y es una herramienta valiosa como factor predictivo y evolutivo de varios trastornos que involucran trastornos del SNA. La acupuntura se emplea como tratamiento único en diversos trastornos cardiovasculares. Los puntos C7 y en menor grado B6 se emplean en el tratamiento de diversas enfermedades cardiovasculares como medida única o complementario. El objetivo de esta investigación es comparar el efecto de los puntos C7 versus B6 en la variabilidad de la frecuencia cardiaca en adultos sanos. Materiales y métodos Se realizó un estudio experimental, de corte transversal, comparativo y abierto. Se reclutaron 12 voluntarios sanos que se dividieron en dos grupos: el primero para estudiar el efecto de C7 constituido por 6 sujetos (2/4 mujeres/varones) con edad 26 ± 4.7 (media ± DE); el segundo para estudiar el efecto de B6 constituido por 6 sujetos (5/1 mujeres/varones) con edad 28 ± 6.5 (media ± DE). El protocolo de investigación lo aprobó el Comité de Ética de la Institución y estuvo apegado a la Declaración de Helsinki respecto a la investigación biomédica en humanos. A cada uno de los 12 participantes se les asignó de manera aleatoria a uno de los dos grupos experimentales. Los sujetos permanecieron en reposo en decúbito dorsal en un periodo de estabilización de 5 min; a continuación se realizaron tres registros de 5 min de las etapas preacupuntura, transacupuntura y posacupuntura. Para el cálculo de la variabilidad de la frecuencia cardiaca (VFC) se realizó un registro electrocardiográfico que se amplificó y digitalizó mediante el equipo SphygmoCor (AtCor Medical, Modelo EM3, Sydney, Australia) y se almacenó en una computadora. Los índices de dominio de frecuencia fueron baja, alta y el cociente baja/alta (LF, HF, LH/HF, de manera respectiva de acuerdo a sus siglas en inglés). Se emplearon agujas de acupuntura (HBW Supply Inc., San Jacinto Hemet, CA, EUA) con 0.30 x 40 mm de diámetro y longitud, de manera respectiva. Se localizaron los puntos de manera tradicional y se introdujo la aguja de manera perpendicular a las profundidades recomendadas; no se realizó estimulación adicional, y la aguja permaneció insertada durante 5 minutos. Para el análisis cinético de los cambios en la frecuencia cardiaca producida por cada uno de los cinco puntos se llevó a cabo un registro continuo de los intervalos RR durante un periodo de 5 min mediante el instrumento Finometer (Finapres Medical Systems, Holanda). Se aplicó acupuntura en cada uno de los puntos estudiados durante el periodo del minuto 6 - 10 del registro. A partir de los intervalos RR se calculó la frecuencia cardiaca; a continuación se obtuvo la primera derivada de la curva de intervalos RR. Resultados Los resultados más notables fueron los siguientes: la acupuntura en C7 produjo aumentos en los periodos de acupuntura y posacupuntura. El empleo de la primera derivada de la curva de intervalos RR mostró que la rapidez máxima del incrementó de los intervalos RR por la aplicación de acupuntura manual en C7 se produjo en el segundo 7.4. Por otra parte, la acupuntura en B6 no originó cambios significativos en los índices estudiados de la VFC. La acupuntura en B6 produjo aumento en el periodo posacupuntura. El empleo de la primera derivada de la curva de intervalos RR mostró que la rapidez máxima del incremento de los intervalos RR por la aplicación de acupuntura manual en B6 se produjo en el segundo 46. La comparación del efecto de estos puntos mostro que C7 y B6 originaron de manera inicial un incremento y una disminución de la duración de los intervalos RR, de manera respectiva. La rapidez del efecto de C7 fue mayor que la de B6; mientras que la magnitud del efecto de C7 fue relativamente mayor que el de B6. Conclusiones La aplicación de los puntos de acupuntura C7 y B6 mostró efectos contrarios sobre la duración de los intervalos RR. El punto C7 originó un incremento de la duración de los intervalos RR de aparición más rápida y mayor intensidad relativa, respecto al efecto de disminución de la duración e intensidad relativa por la acupuntura en el punto B6. Lo que concuerda con las observaciones clínicas de un mayor efecto cardiovascular con la aplicación de C7. Ninguno de los tratamientos con acupuntura en C7 o BP6 originó cambios significativos en la variabilidad de la frecuencia cardiaca. Palabras clave: variabilidad de la frecuencia cardiaca, Corazón 7, Bazo 6, cinética de la acupuntura, intervalos RR.